Salicylic acid alleviates cadmium-induced stress responses through the inhibition of Cd-induced auxin-mediated reactive oxygen species production in barley root tips - Tamás, Ladislav (Journal of plant physiology, 2015)
Copyright © 2014 Elsevier GmbH. All rights reserved.